ANALISIS DAMPAK IMPLEMENTASI ZAKAT DALAM PERENCANAAN PAJAK TERHADAP KEWAJIBAN FISKAL PADA PT. SUNTARJA SEKAYU - Aryani, Farida (Jurnal Ilmiah Akuntansi Rahmaniyah, 2025)
This descriptive study aims to analyze the impact of zakat implementation in tax planning on fiscal obligations and tax efficiency at PT. Suntarja. The research uses secondary data from the company’s 2024 financial statements. The analysis involves calculating zakat and corporate income tax (PPh Badan) payable. Without considering zakat as a deduction from taxable income (PKP), the corporate tax payable amounts to Rp.852,840,560. After applying zakat at 2.5%, the PKP is reduced by Rp.96,913,700, lowering the tax payable to Rp831,519,546. Thus, zakat implementation results in a tax efficiency of Rp.21,321,014. These findings indicate that zakat can be utilized in tax planning to reduce fiscal burdens. It is recommended that companies owned by Muslim stakeholders take advantage of zakat as a deductible expense, not only for fiscal benefits but also to demonstrate compliance with religious values and Islamic economic principles. The government is also encouraged to develop an integrated digital system between zakat payments and taxation to enable automatic and efficient tax deductions when zakat is paid through official channels.